Medical devices in times of pandemic: Efficacy of a high-flow artisanal system in the management of patients hospitalized by COVID-19. - Muñoz del Carpio Toia, Agueda (2023)
Objective: To evaluate the efficacy of the Wayrachi continuous positive airway pressure (CPAP) non-invasive respiratory support device compared to the commercial high-flow cannula (CAF) for the treatment of patients with SARS-CoV-2. Methods: Study carried out at the Honorio Delgado Espinoza Hospital in Arequipa (Hospital COVID-MINSA Arequipa). The medical records of patients with SARS-CoV-2, of moderate or severe severity, who required non-invasive respiratory assistance, hospitalized in the internal medicine service during the 2nd wave of COVID in Peru, were evaluated. A survival analysis was performed considering days to death comparing Wayrachi with CAF. The effect of variables on death was explored using Cox regression. Results: 114 patients treated with Wayrachi (56.44%) and 88 with CAF (43.5%) were evaluated, observing a frequency of death of 34.2% and 34.1%, respectively. When comparing the frequency of death, or its survival, in both managements, no significant difference was observed (p=0.986 and p=0.928), this was maintained in the multivariate model. Conclusion: The Wayrachi CPAP had similar results to those presented by the commercial CAF equipment, which indicates it as an effective option for the management of COVID patients who require non-invasive respiratory support.